Antifungal therapy: New advances in the understanding and treatment of mycosis - Scorzoni, Liliana [UNESP]; de Paula e Silva, Ana C.A. [UNESP]; Marcos, Caroline M. [UNESP]; Assato, Patrï¿½cia A. [UNESP]; de Melo, Wanessa C.M.A. [UNESP]; de Oliveira, Haroldo C. [UNESP]; Costa-Orlandi, Caroline B. [UNESP]; Mendes-Giannini, Maria J.S. [UNESP]; Fusco-Almeida, Ana M. [UNESP] (Frontiers, 2017)
The high rates of morbidity and mortality caused by fungal infections are associated with the current limited antifungal arsenal and the high toxicity of the compounds. Additionally, identifying novel drug targets is challenging because there are many similarities between fungal and human cells. The most common antifungal targets include fungal RNA synthesis and cell wall and membrane components, though new antifungal targets are being investigated. Nonetheless, fungi have developed resistance mechanisms, such as overexpression of efflux pump proteins and biofilm formation, emphasizing the importance of understanding these mechanisms. To address these problems, different approaches to preventing and treating fungal diseases are described in this review, with a focus on the resistance mechanisms of fungi, with the goal of developing efficient strategies to overcoming and preventing resistance as well as new advances in antifungal therapy. Due to the limited antifungal arsenal, researchers have sought to improve treatment via different approaches, and the synergistic effect obtained by the combination of antifungals contributes to reducing toxicity and could be an alternative for treatment. Another important issue is the development of new formulations for antifungal agents, and interest in nanoparticles as new types of carriers of antifungal drugs has increased. In addition, modifications to the chemical structures of traditional antifungals have improved their activity and pharmacokinetic parameters. Moreover, a different approach to preventing and treating fungal diseases is immunotherapy, which involves different mechanisms, such as vaccines, activation of the immune response and inducing the production of host antimicrobial molecules. Finally, the use of a mini-host has been encouraging for in vivo testing because these animal models demonstrate a good correlation with the mammalian model; they also increase the speediness of as well as facilitate the preliminary testing of new antifungal agents. In general, many years are required from discovery of a new antifungal to clinical use. However, the development of new antifungal strategies will reduce the therapeutic time and/or increase the quality of life of patients.
Keywords: Alternative animal models; Antifungal drugs; Antifungal resistance; Biofilms; Fungal vaccine; Nanoparticles; New antifungal therapy